2009
DOI: 10.4049/jimmunol.0803849
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Soluble Vascular Endothelial Growth Factor Receptor-1 in Human Monocyte-Derived Mature Dendritic Cells Contributes to Their Antiangiogenic Property

Abstract: The soluble form of vascular endothelial growth factor receptor-1 (sVEGFR-1) is produced from endothelial cells by alternative splicing of VEGFR-1 mRNA, and can inhibit angiogenesis by blocking the biological effects of VEGF. In this study, we show the expression of a large amount of sVEGFR-1 in human monocyte-derived mature dendritic cells (mDCs). As compared with monocytes and immature DCs, mDCs generated by TNF-α or soluble CD40L with IFN-γ, but not LPS or other stimuli, preferentially produce sVEGFR-1. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…A recent interesting study showed that monocytederived human mature DCs activated by TNF-a or soluble CD40L with IFN-g, but not immature ones, expressed considerable amount of sFLT-1 and showed antiangiogenic potential, significantly inhibiting tumor growth of immunodeficient mice (32). Similar positive function of DC-derived sFLT-1 against VEGF-A/VPF was also reported by other groups (33), suggesting that mature DCs might be resistant to VEGF-A/VPF-mediated functional suppression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent interesting study showed that monocytederived human mature DCs activated by TNF-a or soluble CD40L with IFN-g, but not immature ones, expressed considerable amount of sFLT-1 and showed antiangiogenic potential, significantly inhibiting tumor growth of immunodeficient mice (32). Similar positive function of DC-derived sFLT-1 against VEGF-A/VPF was also reported by other groups (33), suggesting that mature DCs might be resistant to VEGF-A/VPF-mediated functional suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The method by which SCID mouse splenocytes were harvested was the same as that of rat splenocytes. Human PBMCs (MNC) were obtained from leukocytes in lymphocyte separation medium (Litton Bionetics, Kensington, MD) as previously described (42). Leukocytes were separated from peripheral blood of healthy donors using an RS-6600 rotor of a Kubota KR-400 centrifuge (Kubota, Tokyo, Japan).…”
Section: Preparation Of Effector Cellsmentioning
confidence: 99%
“…Soluble Flt1 (sFlt1), a circulating form of VEGF-R1 that lacks the transmembrane domain of the intact protein, results from an alternative splicing of VEGF-R1 and also likely results from the cleavage of membrane-bound Flt1 ectodomain by the disintegrin and metalloproteinase/TNF-a-converting enzyme (ADAM/TACE) family of metalloproteases. 17 sFlt1 is mainly secreted by monocytes, 18,19 endothelial cells, and placental cytotrophoblasts 20 and displays potent inhibitory effects on VEGF. Elevated levels of sFlt1 lead to functional VEGF deficiency and promote an effective antiangiogenic state, which may be of significant clinical importance, as demonstrated by the association of elevated serum sFlt1 levels with placental vascular dysfunction and preeclampsia.…”
mentioning
confidence: 99%